2018
DOI: 10.1002/ecs2.2105
|View full text |Cite
|
Sign up to set email alerts
|

Homogenization of plant diversity, composition, and structure in North American urban yards

Abstract: Abstract. Urban ecosystems are widely hypothesized to be more ecologically homogeneous than natural ecosystems. We argue that urban plant communities assemble from a complex mix of horticultural and regional species pools, and evaluate the homogenization hypothesis by comparing cultivated and spontaneously occurring urban vegetation to natural area vegetation across seven major U.S. cities. There was limited support for homogenization of urban diversity, as the cultivated and spontaneous yard flora had greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 68 publications
(150 reference statements)
2
73
2
Order By: Relevance
“…, Groffman ). For example, previous research in the United States has demonstrated urban homogenization by showing that yard floras are compositionally and structurally more similar than the corresponding floras in surrounding natural areas (Wheeler , Pearse ). However, biotic homogenization might also be assessed within and across cities, by comparing the relative similarities of different components of vegetation among yards or other urban habitats (Lososová et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…, Groffman ). For example, previous research in the United States has demonstrated urban homogenization by showing that yard floras are compositionally and structurally more similar than the corresponding floras in surrounding natural areas (Wheeler , Pearse ). However, biotic homogenization might also be assessed within and across cities, by comparing the relative similarities of different components of vegetation among yards or other urban habitats (Lososová et al.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, non‐native species also have the potential to increase phylogenetic diversity and species richness. Cultivated and spontaneous non‐native species in yards are affected by different filtering and sorting processes (Groffman , Pearse ) and may thus have contrasting effects on the composition of yard floras. A critical gap remains in our understanding of the influence of non‐native species on community assembly in urban plant communities and their role in shaping composition and diversity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, such tenants as the 10-20-30 rule (Santamour 1990) are subject to misinterpretation when based on data collected using different sampling intensities (Kendal et al 2014). For example, Pearse et al (2018) collected data from 21 to 30 urban household yards and 3 to 6 natural area sites in their study of ecological homogenization across seven metropolitan areas. Thus, evaluating the effectiveness of this rule requires certainty when estimating the proportion of individuals in each species, each genus, and each family.…”
Section: Discussionmentioning
confidence: 99%
“…Previous urban ecology studies that test the hypothesis of ecological homogenization have used Jaccard's index (McKinney 2006), Sørensen's index (Pearse et al 2018 (Yang et al 2017, Avolio et al 2018, and a variety of qualitative methods, as well as specifically designed protocols which have included data on herbaceous vegetation and soils (Groffman et al 2014). Our study, which further incorporated disparate data sources, demonstrates that the Raup-Crick dissimilarity indices, based on presence/absence data, are robust to sampling differences.…”
Section: Discussionmentioning
confidence: 99%